Erbium ion implantation into diamond – measurement and modelling of the crystal structure. Issue 8 (14th February 2017) - Cajzl, Jakub; Nekvindová, Pavla; Macková, Anna; Malinský, Petr; Sedmidubský, David; Hušák, Michal; Remeš, Zdeněk; Varga, Marián; Kromka, Alexander; Böttger, Roman; Oswald, Jiří
Abstract : Doping of diamond with erbium as an optically active centre. Abstract : Diamond is proposed as an extraordinary material usable in interdisciplinary fields, especially in optics and photonics. In this contribution we focus on the doping of diamond with erbium as an optically active centre. In the theoretical part of the study based on DFT simulations we have developed two Er-doped diamond structural models with 0 to 4 carbon vacancies in the vicinity of the Er atom and performed geometry optimizations by the calculation of cohesive energies and defect formation energies. The theoretical results showed an excellent agreement between the calculated and experimental cohesive energies for the parent diamond. The highest values of cohesive energies and the lowest values of defect formation energies were obtained for models with erbium in the substitutional carbon position with 1 or 3 vacancies in the vicinity of the erbium atom. From the geometry optimization the structural model with 1 vacancy had an octahedral symmetry whereas the model with 3 vacancies had a coordination of 10 forming a trigonal structure with a hexagonal ring. In the experimental part, erbium doped diamond crystal samples were prepared by ion implantation of Er + ions using ion implantation fluences ranging from 1 × 10 14 ions per cm 2 to 5 × 10 15 ions per cm 2 . The experimental results revealed a high degree of diamond structural damage after the ion implantation process reaching up to 69% of disordered atoms in the samples. The prepared Er-doped diamond samples annealed at the temperatures of 400, 600 and 800 °C in a vacuum revealed clear luminescence, where the 〈110〉 cut sample has approximately 6–7 times higher luminescence intensity than the 〈001〉 cut sample with the same ion implantation fluence. The reported results are the first demonstration of the Er luminescence in the single crystal diamond structure for the near-infrared spectral region.